Long-Delayed Manifestation of COVID-19 Coagulopathy Presenting with Severe Cerebral Venous Thrombosis Causes Massive Brain Hemorrhage - Tjahjadi, Mardjono; Caropeboka, Sinatrya; Permana, Christian; Susanto, Krisandi; Susanto, Eka (Asian Journal of Neurosurgery, 2022)
COVID-19 infection causes coagulopathy, which may lead to cerebral venous thrombotic (CVT) event. It usually occurs in patients with higher severity level of infection and manifests mostly within a month after the infection. However, in rare cases, the CVT may happen long after the infection and unrelated to the degree of the infection severity. We present the case of a previously healthy 62-year-old male patient with very mild COVID-19 symptoms that resolved in 3 weeks of home isolation treatment. Immediately after the infection, he developed hypercoagulability and was treated routinely with a novel oral anti-coagulant drug. Four months after the infection, he developed a worsening headache which, in several days, deteriorated to cause reduction in his consciousness level. Imaging showed a right temporoparietooccipital massive brain hemorrhage with right transverse and sigmoid sinus thrombosis. Emergency decompressive craniectomy was performed and the patient recovery was excellent. In patients with a hypercoagulable state after COVID-19 infection, the possibility of CVT event should be observed. It may not be related to the severity of the infection, and it may happen long after the infection.
Keywords: cerebral venous thrombosis; COVID-19; long covid; decompressive craniectomy